Ferret animal model of corneal endothelial dysfunction for evaluation of drug effect on corneal endothelial wound healing - KITANO, Junji; OKUMURA, Naoki; HOSHI, Nobuhiko; YAMAMOTO, Mayumi; SAKAMOTO, Yuji; NUMATA, Ryouhei; KOIZUMI, Noriko; KOMADA, Takafumi (Animal Eye Research, 2013)
The purpose of our research is to establish a new experimental animal model for evaluating the effect of novel medications on corneal endothelial dysfunction. Until recently, rabbit have been widely used for most of the basic corneal endothelial research. However, since the corneal endothelial cells of rabbit proliferate sufficiently after damage, these animals are not suitable for the evaluation of long-term progress. Researchers in our group developed a monkey model of corneal endothelia dysfunction in which the corneal endothelium exhibits limited proliferative ability in vivo. However, monkey are not readily used for research purposes, both because they are difficult to handle and for ethical reasons. For all of these reasons, we have focused on the ferret as a candidate for development of a corneal endothelial dysfunction model; we consider that this species may act as a kind of intermediate model between rabbit and monkey. In this study, we made corneal endothelial wounds in ferret by transcorneal freezing and investigated whether a selective Rho-kinase (ROCK) inhibitor Y-27632 enhanced corneal endothelial wound healing. Our clinical observation showed that the topical eye drops of Y-27632 improved the corneal edema and opacity. The mean wound area was signifi cantly (p<0.01) reduced in the Y-27632 treated eyes (16.3±3.0 %) compared to the control eyes after 48 hours. The density was significantly (p<0.05) higher in the ROCK inhibitor treated eyes compared to that in the control eyes (1836.3 ± 706.1 and 1149±597.9, respectively) and the corneal endothelial cell formed a continuous polygonal monolayer. Our results indicated that we established a new experimental animal model for corneal endothelial dysfunction in ferret and showed that this model was applicable for evaluating the effect of novel medications on corneal endothelial dysfunction.